Les murs parlent de nous. Esthétique politique des singularités quelconques - Alain Bertho (Cahiers de Narratologie)
The graphic interventions on the walls of cities should be read as statements in situations. Political aesthetics of riots and insurrections of 2011 or localized urban statement of dissent, these pictures contemporaneously articulate singular and common, the local and the global. They fit the « pictorial turn » in the breakdown of social and political groups that marked the end of the 20th century. The investigation into his public image opens a new field for ethnology and raises new writing requirements.